'Milih Dino' Culture in Pringapus Trenggalek and its Impact on Individual Psychology: Budaya ‘Milih Dino’ di Pringapus Trenggalek dan Dampaknya pada Psikologis Individu - Risky , Achamad; Himmatul , Firda; Dwi , Ristanti; Mahestika , Vanessa; Susilo, Joko (Universitas Muhammadiyah Sidoarjo, 2024)
Choosing the right day and month in Javanese culture is a meaningful tradition, full of cultural values ​​and beliefs passed down from generation to generation. This tradition not only serves as a guide for determining the time for important events such as weddings, circumcisions and other ceremonies, but also helps build the cultural identity of the Javanese people. This article discusses the origins, methods, and benefits of this tradition and how it has been preserved in the modern era. Additionally, this article also looks at how the